لغة فورث و مميزاتها كلغة تعريفية للمكونات المادية الافتراضية - شامل عبد الستار سليمان (PROSPECTIVE RESEARCHES, 2023)
Forth language let programmers to define the hardware in the same language they write software in. The hardware that define in Forth can be verified by executing the hardware definition words, at the command line or by writing special words in Forth to test their operations.